Biodiversidade dos parasitas de peixes provenientes do rio Sapucaí-Mirim, Estado de São Paulo, Brasil - Zago, Aline Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Recently, parasites have been recognized as important components of global biodiversity because the important roles played by these organisms in natural ecosystems. Although knowledge about the diversity of parasites has increased in recent decades, the number of parasite species of fishes in Brazil is relatively low compared to the biodiversity of host species. Thus, this study aimed to survey the biodiversity of fish parasites from four sampling sites in an area under the influence of Small Hydroelectric Power Plants in the Sapucaí-Mirim River, São Paulo State, Brazil, as well as to evaluate the structure of metazoan parasite communities of Characiformes and four species of Leporinus sp. From March 2012 to July 2013, 462 fish specimens of 16 species of Characiformes, Siluriformes, Perciformes, and Gymnotiformes were collected. It was observed that 86.58% of fish specimens were parasitized by at least one metazoan parasite taxon. The parasites found belonged to eight different groups (Myxozoa, Monogenea, Digenea, Cestoda, Nematoda, Acantocephala, Arthopoda and Annelida) and a total of 6,830 parasites were collected and analyzed. Ninety-seven parasite taxa were found, and Monogenea was the group that had the highest number of species, followed by Nematoda and Digenea. The parasite communities of Characiformes showed mainly differences among the host species, although belonging to the same order or family. The sampling site, condition factor and the host body size also influenced the distribution of parasite abundance of some fish species analyzed. The metazoan parasite communities of Leporinus spp. primarily showed differences among the host species, wherein the infracommunities of Leporinus amblyrhynchus and Leporinus elongatus tended to be more similar, as well as Leporinus friderici and Leporinus octofasciatus. New locality records are made to all parasite species collected and were also found new parasite species and are made new occurrence records on different hosts for several parasite species.

Nos últimos anos, os parasitas foram reconhecidos como importantes componentes da biodiversidade global, dado os importantes papéis desempenhados por esses organismos em ecossistemas naturais. Embora o conhecimento sobre a diversidade de parasitas tenha aumentado nas últimas décadas, o número de espécies de parasitas de peixes no Brasil é relativamente baixo quando comparado com a biodiversidade das espécies hospedeiras. Desta forma, o presente trabalho teve como objetivo realizar um levantamento da biodiversidade dos parasitas de peixes procedentes de quatro locais em uma área sob a influência de Pequenas Centrais Hidrelétricas (PCHs) no rio Sapucaí-Mirim, Estado de São Paulo, Brasil, bem como avaliar a estrutura das comunidades de metazoários parasitas de peixes Characiformes e de quatro espécies do gênero Leporinus. Durante o período de março de 2012 a julho de 2013, foram coletados 462 espécimes pertencentes a 16 espécies de peixes das ordens Characiformes, Siluriformes, Gymnotiformes e Perciformes. Observou-se que 86,58% dos espécimes estavam parasitados por pelo menos um taxon de metazoário parasita. Os parasitas encontrados pertenciam a oito diferentes grupos (Myxozoa, Monogenea, Digenea, Cestoda, Nematoda, Acantocephala, Arthopoda e Annelida), sendo coletado um total de 6.830 parasitas. Noventa e sete taxa de parasitas foram encontrados, sendo que a classe Monogenea foi o grupo que apresentou o maior número de espécies, seguido do filo Nematoda e da sub-classe Digenea. As comunidades parasitárias dos Characiformes apresentaram principalmente diferenças entre as espécies hospedeiras, embora pertencendo a mesma ordem ou família. O local de amostragem, o fator de condição e o tamanho do hospedeiro também influenciaram na distribuição da abundância parasitária de algumas espécies analisadas. As comunidades de parasitas de Leporinus spp. apresentaram principalmente diferenças entre as espécies hospedeiras, sendo que as infracomunidades de Leporinus amblyrhynchus e Leporinus elongatus tenderam a ser mais similares, assim como as de Leporinus friderici e Leporinus octofasciatus. Todas as espécies de parasitas coletados constituem-se de novos registros de localidade, sendo que também foram encontradas espécies novas e foram feitos novos registros de ocorrência em diferentes hospedeiros para várias espécies de parasitas.
Biodiversity of parasites of fishes from the Sapucaí-Mirim River, São Paulo State, Brazil
Keywords: Variation partitioning method; Helminths; Monogenea; Nematoda; Digenea; Árvore de regressão multivariada (MRT); Método do particionamento da variação; Helmintos; Monogenea; Nematoda; Digenea; Multivariate regression trees (MRT)